Location and Associated Carbon Storage of Erosional Escarpments of Seagrass Posidonia Mats - Serrano, Oscar; Lavery, Paul S.; López-Merino, Lourdes; Ballesteros, Enric; Mateo, Miguel A. (Frontiers in Marine Science, 2016)
Seagrasses of the genus Posidonia can form an irregular seascape due to erosional processes exposing thick walls of organic matter-rich soils. However, little is known about the location and characteristics of these particular formations. Here we provide comprehensive estimates of organic carbon (Corg) storage in P. oceanica and P. australis meadows, while providing insight into their location and mechanisms of formation, and highlighting future research directions. Erosional reef escarpments are restricted to shallow highly productive P. oceanica meadows from the Mediterranean Sea and P. australis meadows from the Indian Ocean, and sustain the existence of Corg-rich deposits in surrounding meadows. The thickness of the mat escarpments can reach up to 3 m and their length can vary from few to hundreds meters. Mechanisms of formation appear to differ among sites, from naturally-induced escarpments by wave action and/or tidal flow to human-induced escarpments by dredging activities. The inter-twined remains of seagrass shoots within the sediment matrix consolidate the sandy substrate and hold the exposed Posidonia mat escarpments together, maintaining a semi-rigid structure. This phenomenon is unusual but of exceptional importance in marine biogeochemical cycles, revealing the largest Corg sinks among seagrasses worldwide (ranging from 15-176 kg Corg m-2 in 2 m-thick mats accumulated at 2-249 g Corg m-2 yr-1 over 300 to 3000 yr).